Avventure e disavventure dei processi di co-sviluppo - Bruno Riccio (EtnoAntropologia)
"Co-development" is the term to name those aid projects where migrants present themselves as "actors of development. Those programmes involve also local government, migrant and non-migrant associations and NGOs. After a brief glance towards the debate over transnational migration and development nexus, I focus on the different perspectives towards co-development and, relying on some examples, on the ambivalent nuances characterizing such projects. Nevertheless, I argue that these projects are an interesting subject of study, which provides a fruitful methodological solution to observe the interplay between associations and institutions in the receiving context, various transnational practices and the economic and socio-cultural changes in the context of origin.